FEATURES OF THE ACTIVITIES OF INFRASTRUCTURE NATURAL MONOPOLIES - CHOBITOK, Viktoriia; KOSTIN, Yuriy (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article defines the principles of supplier strategies operationalization in the Ukrainian energy market. It has been proven that the basis of the organizational and economic mechanism for the implementation of the strategy is to put the principle of «clienteering». Its main components should be the parameters of service provision that are important for the client. These components are: 1) price competitiveness; 2) reputation and trust; 3) quality of service; 4) additional opportunities. In the future, each component is specified in business processes that contribute to the achievement of the specified parameters. Thus, the supplier’s reputation and trust in it are strengthened by publishing information important to the consumer (tariff plans, licenses, reporting, information about the supplier and traders), organizing modern communication channels (chatbots, messengers, round-the-clock support, social media pages networks), participation in public initiatives. The quality of the service is closely related to digitalization (creation of mobile applications, personal client offices, remote work with contracts, introduction of online payment and online support), creation of combined products and formation of regional networks - client and partner. Additional capabilities provide for the launch of business processes, how to turn a customer into a service provider of a supplier. The analysis of organizational and economic mechanisms for the implementation of supplier strategies in the Ukrainian energy market showed that they are built according to similar principles. Their weak point is the absence or fragmentation of business processes that strengthen the supplier’s reputation and increase trust in it. The sample included suppliers that focus on the development of the retail segment, including household consumption, and released their price offers in August 2022. It was found that independent suppliers that seek to expand the package of digital services are able to successfully compete even with those companies that which rely on state support in forming a client base.